Entropy Production in the Diffusion-Driven Regime of Droplet Evaporation - Bulavin, L. A.; Verbins’ka, G. M.; Gavryushenko, D. A.; Sysoev, V. M.; Solov’yov, O. S.; Cherevko, K. V. (Ukrainian Journal of Physics, 2018)
A consistent model describing the evaporation of a spherical droplet has been developed. Expressions for the total flux and production of entropy have been obtained in the case of ideal solution with regard for the concentration dependence of the diffusion coefficient. The results obtained allow the stabilizing effect for the entropy production and flux to be revealed even in the case where only the entropy contributions to thermodynamic potentials at the mixing are taken into account.